2015
DOI: 10.1245/s10434-015-4714-x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy for Breast Cancer, Is Practice Changing? A Population-Based Review of Current Surgical Trends

Abstract: A significant increase in the use of neoadjuvant chemotherapy over time was identified, and treatment with mastectomy as definitive surgical management remained high. There was significant variability in neoadjuvant chemotherapy use by the operating surgeons, in addition to factors generally associated with more locally advanced/aggressive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…The incidence of nast in British Columbia is similar to that in other reports, including the reported 3.8% use of nast in 4 large U.S. treatment centres 20 and the 8.5% use in another Canadian province 21 . Use of nast was quite a bit lower than in another American study, which reported a nast rate of 17.4% 22 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The incidence of nast in British Columbia is similar to that in other reports, including the reported 3.8% use of nast in 4 large U.S. treatment centres 20 and the 8.5% use in another Canadian province 21 . Use of nast was quite a bit lower than in another American study, which reported a nast rate of 17.4% 22 .…”
Section: Discussionsupporting
confidence: 87%
“…Use of nast was quite a bit lower than in another American study, which reported a nast rate of 17.4% 22 . All of those studies demonstrated variability by stage, centre 20 , surgeon 21 , and geographic region 22 , as in our cohort, for whom use of nast varied by cancer centre-a finding showing that, despite widely published guidelines 23,24 , potential biases based on region and training can affect patient care.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Une étude récente a évalué les changements de pratique au Canada et a montré que le taux de CNA était passé de 7,4 % en 2012 à 10,4 % en 2014 [7]. Cependant, le seul bénéfice direct démontré pour le patient est à ce jour limité à son impact sur la stratégie locorégionale, puisque les survies ne sont pas statistiquement différentes actuellement (par rapport à la chirurgie première) et qu'aucune étude n'a montré de bénéfice à changer de protocole de chimiothérapie en cas de réponse insuffisante.…”
unclassified